Database systems : the complete book - Molina, Hector Garcia-; Ullman, Jeffrey ;Widom, Jennifer (Singapore : Pearson Education, 2009)
This introduction to database systems offers a readable comprehensive approach with engaging, real-world examples -- users will learn how to successfully plan a database application before building it.
The worlds of database systems -- I. Relational Database Modeling -- II. Relational Database Programming -- III. Modeling and programming for semistructured data -- IV. Database System Implementation -- V. Other Issues in Management of Massive Data.
Includes index.
Keywords: DATABASE MANAGEMENT